Keabsahan Penggunaan Campuran Air dan Cairan Antiseptik Perspektif Fikih Taharah (Studi Komparatif Mazhab Hanafi dan Syafii): The Validity of Using a Mixture of Water and Antiseptic Liquid from a Taharah Fiqh Perspective (Comparative Study of the Hanafi and Syafii Schools) - Mahmuddin, Ronny; Rustam Efendi; Abd. Fattah Fathurozzy (DIRASAH: Jurnal Kajian Islam, 2024)
This study aims to determine and understand the validity of the use of water mixed with antiseptic from the perspective of taharah fiqh according to the views of the Hanafi and Syafii schools. This study uses a qualitative descriptive research type (non-statistical) using the library research method (literature review) which focuses on the study of manuscripts and texts, using the descriptive method of comparative study analysis. The results of this study indicate that there are differences in views between the Hanafi and Syafii schools on the validity of the use of water mixed with antiseptic for taharah. First, the Hanafi school views water mixed with antiseptic liquid as holy and purifying. While the Syafii school views water mixed with antiseptic liquid as holy but not purifying. Second, the Hanafi school of thought and the Syafii school of thought differ regarding changes in the nature of water to the standard of whether the water is still purifying or not. In the view of the Hanafi school of thought, changing one of the properties of water does not eliminate the standard of purification, whereas in the Syafii school of thought changing one of the properties is enough to make the water lose its standard of purification. Third, both schools of thought agree that if a sacred object and water are mixed and the sacred object becomes dominant then the standard for purifying it will disappear. The arguments used by the two schools of thought all come from the Al-Qur'an and Sunnah and the opinions of the ulama, but the cause of differences of opinion is the interpretation and understanding of these arguments.